Robin George Collingwood on metaphysics as understanding the world - Hagiu, Adrian; Lupașcu, Constantin; Bortoș, Sergiu (Technium Social Sciences Journal, 2023)
The aim of our study is to provide an overview of the concept of metaphysics as conceived by the British philosopher Robin George Collingwood and argue that his method still holds practical implications for contemporary philosophers. According to Collingwood, metaphysics is the science – that is, the knowledge – of the absolute presuppositions of an historical period. In other words, for him metaphysics is a historical science, albeit one which is not confounded with history. Thus, following the discussion concerning the constitution of Collingwood’s metaphysics, and a brief framing of his thought within the history of metaphysics, we will make the case in favor of the thesis that understanding or knowing the absolute presuppositions or principles of a historical period provides the individual with a vision of that period. As such, we will also advocate that the duty of those philosophers who wish to explain our contemporary world is to identify these principles. In order to achieve the objectives outlined in our study, we have employed both the hermeneutic analysis and the phenomenological description as our methods of choice. The results of our investigation serve a practical purpose in contemporary philosophy, as the individual who succeeds in shaping the metaphysics of our current time period is in fact shaping his own vision – Weltanschauung – of the contemporary world, his own ideas, principles or beliefs. Therefore, our study can be of great benefit to the reader who is interested in the metaphysics of the present, and the social changes it entails, precisely because it provides the necessary tools for this particular process of knowledge.